Maximizing the Implementation of Collaborative Learning to Improve Students’ Reading Comprehension - Mantra, Ida Bagus Nyoman; Sri Widiastuti, Ida Ayu Made (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
Reading is one of the language skills that needs to be mastered by the students in language learning to enable students to communicate in English effectively. Consequently, teachers are encouraged to implement appropriate teaching methods to ensure that the learning activities become effective in reading comprehension classes. This study used classroom action research to build up the students’ reading comprehension through collaborative learning. Data from the study were collected through pre-test, post-test, and questionnaire. The results showed that the student's reading comprehension of the seventh-grade students could be improved through collaborative learning. Therefore, collaborative learning is considered very effective for teaching reading comprehension. This study implies that teachers should consider using collaborative learning to enhance students' reading comprehension.